Liposomal Ellagic Acid Alleviates Cyclophosphamide-Induced Toxicity and Eliminates the Systemic Cryptococcus neoformans Infection in Leukopenic Mice - Masood Alam Khan; Arif Khan; Mohd Azam; Khaled S. Allemailem; Faris Alrumaihi; Ahmad Almatroudi; Fahad A. Alhumaydhi; Faizul Azam; Shaheer Hasan Khan; Syeda Fauzia Farheen Zofair; Sumbul Ahmad; Hina Younus (MDPI AG, 2021)
Cryptococcus neoformans infections rose sharply due to rapid increase in the numbers of immunocompromised individuals in recent years. Treatment of Cryptococcosis in immunocompromised persons is largely very challenging and hopeless. Hence, this study aimed to determine the activity of ellagic acid (EA) in the treatment of C. neoformans in cyclophosphamide injected leukopenic mice. A liposomal formulation of ellagic acid (Lip-EA) was prepared and characterized, and its antifungal activity was assessed in comparison to fluconazole (FLZ). The efficacy of the drug treatment was tested by assessing survival rate, fungal burden, and histological analysis in lung tissues. The safety of the drug formulations was tested by investigating hepatic, renal function, and antioxidant levels. The results of the present work demonstrated that Lip-EA, not FLZ, effectively eliminated C. neoformans infection in the leukopenic mice. Mice treated with Lip-EA (40 mg/kg) showed 70% survival rate and highly reduced fungal burden in their lung tissues, whereas the mice treated with FLZ (40 mg/kg) had 20% survival rate and greater fungal load in their lungs. Noteworthy, Lip-EA treatment alleviated cyclophosphamide-induced toxicity and restored hepatic and renal function parameters. Moreover, Lip-EA treatment restored the levels of superoxide dismutase and reduced glutathione and catalase in the lung tissues. The effect of FLZ or EA or Lip-EA against C. neoformans infection was assessed by the histological analysis of lung tissues. Lip-EA effectively reduced influx of inflammatory cells, thickening of alveolar walls, congestion, and hemorrhage. The findings of the present study suggest that Lip-EA may prove to be a promising therapeutic formulation against C. neoformans in immunocompromised persons.